Chuyển đổi số ngành thông tin khoa học và công nghệ để hội nhập quốc tế - Tạ, Tuấn Anh (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article summarizes the development of science and technology information system in Vietnam, the strategy and platform required to manage national S&T information and then providing digital transformation solutions for international integration.